Dirofilaria repens: emergence of autochthonous human infections in the Czech Republic (case reports). Issue 1 (December 2016) - Matějů, Jana; Chanová, Marta; Modrý, David; Mitková, Barbora; Hrazdilová, Kristýna; Žampachová, Víta; Kolářová, Libuše
Abstract Background Human dirofilariasis is a zoonotic infection that continues to spread to previously unaffected areas of Europe. In the South Moravian Region of the Czech Republic (CR), imported as well as autochthonous canine infections were recorded in the last decade, and parasite DNA was detected in mosquitoes ofAedes vexans . In the present paper, humanDirofilaria infections are reported from the country for the first time. Case presentation The samples from five patients with suspected tissue helminthiases were investigated. In particular cases, nematodes were isolated from various tissues including skin of lower leg, soft tissues of finger, subcutaneous tissue of hypogastrium, lymph node and peritoneum. The diagnosis was based on light microscopic morphology and/or DNA analysis of the worms. In addition, ELISA examination of patients' sera for anti-filaria IgG antibodies was performed. Conclusions In the CR, five cases of human dirofilariasis caused byDirofilaria repens were recorded during 2010–2014 (species determination for three of them was confirmed besides morphological also by DNA analysis). At least, three of the cases were of autochthonous origin (the patients are Czech citizens residing in South Moravian Region who have never travelled abroad). The findings confirm the natural setting ofD. repens in South Moravian Region of the CR. Dirofilariasis should be therefore considered as endemic in this area where it may represent a significant risk factor for public health.